Regioselectivity and Reactivity of Intramolecular [2+2] Cycloaddition Reactions of Acyl Ketenes: Experimental and Theoretical Studies - Zahedifar, Mahboobeh; Sheibani, Hassan; Saheb, Vahid (Synlett, 2018)
The regioselectivity of the intramolecular [2+2] cycloaddition reaction of acyl ketenes formed from metastable mesoionic 1,3-oxazinium-4-olates was investigated by experimental and theoretical methods. The ring opening of the mesoionic N-allyl-2-(2-arylvinyl)-1,3-oxazinium-4-olates led to the formation of unstable acyl ketenes. Although there are four possible paths for an intramolecular [2+2] cycloaddition reaction involving the two double bonds (vinyl and allyl), only the intramolecular [2+2] criss-cross cycloaddition reaction through the vinyl double bond occurred to give 3-allyl-3-azabicyclo[3.1.1]heptane-2,4,6-trione derivatives. These products were not formed when a strongly electron-withdrawing group was present on the aryl group of acrylamides or benzamides. To understand the mechanism of the reaction, density functional theory calculations at the M06-2X/6-31+G(d) level were performed. These revealed that the formation of some preliminary intermediates plays a significant role in the formation of mesoionic 1,3-oxazinium-4-olates.
Keywords: chlorocarbonylphenylketene; oxazinium olates; [2+2] cycloaddition; acyl ketenes; density functional theory